Energy Budget on Various Land Use Areas Using Reanalysis Data in Florida - Chi-Han Cheng; Fidelia Nnadi; Yuei-An Liou (Advances in Meteorology)
Energy budget is closely related to the hydrological cycle through evapotranspiration (ET) or latent heat. Hence, quantifying the energy budget on different land uses is critical for understanding the water budget and providing useful land use information for decision makers. However, traditional methods, including in situ measurements and model-only approaches, have deficiencies in data availability, and we have still not yet fully realized how well the energy budgets presented in reanalysis data sets. Therefore, in this study, North American regional reanalysis (NARR) data set from 1992 to 2002 were employed to investigate the energy budget on various land uses (lake, wetland, agriculture, forest, and urban) at a regional scale in Florida. The results showed that the lake and urban areas had high values of energy budget, evaporation, and low Bowen ratio, while the wetland areas have the opposite treads because of the lowest evaporation rate. During drought periods, Bowen ratio, surface temperature, and sensible heat were becoming higher than those of normal years conditions. Finally, by comparing with the observed data, we found NARR had better assimilation of precipitation observations and demonstrated the land use effects from the different coefficient of correlation relationships.